SOCIAL MEDIA MARKETING ON CAMPUS - I Nyoman Tri Sutaguna; Muhammad Yusuf AR; Mashudi Hariyanto; Geofakta Razali; Arief Yanto Rukmana (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
Universities are using social media more creatively in their marketing as a result of digitalization. However, there are few theoretical models that explain the success of social media marketing (SMM) in educational institutions, particularly Instagram. This study seeks to address a theoretical need by concentrating on four variables: QMS, brand awareness, product image, and brand attitude. A poll of 141 Gen Y and 17-27-year-olds was used to acquire quantitative data. The data was then examined using the SmartPLS Statistics tool and Structural Equation Modeling (SEM). Three key findings emerge from the data analysis. First, QMS has a significant and positive influence on brand attitude, brand awareness and brand image.